Prognostic value of high-sensitivity versus conventional cardiac troponin T assays among patients with type 2 diabetes mellitus undergoing maintenance hemodialysis - Keller, Till; Genser, Bernd (American journal of kidney diseases, 2018)
Background - Mortality is high among patients undergoing hemodialysis for whom cardiac troponin concentration is a strong predictor of outcome. Modern troponin assays allow measurement of very low concentrations. - Study Design - Using data from a randomized controlled trial, a cohort analysis to evaluate the prognostic value of very low cardiac troponin T (TnT) concentrations. - Setting & Participants - 1,255 patients with end-stage renal disease and type 2 diabetes mellitus undergoing maintenance hemodialysis from the German Diabetes and Dialysis Study (4D) who had a median follow-up of 4 years. - Index Test, Reference Test, and Outcome - Cardiac TnT was measured using a high-sensitivity assay (hs-TnT) and a conventional assay (conventional TnT) in a subpopulation (n=1,034) with valid measurements for both assays. Outcome measures were all-cause mortality and a composite cardiovascular end point including cardiac death, myocardial infarction, or stroke. - Results - Among the 1,034 study participants, 505 died and 377 had a cardiovascular event. Both hs-TnT and conventional TnT concentrations were associated with mortality and cardiovascular events in models adjusted for cardiovascular risk factors and dialysis-associated variables. 455 (44%) patients with very low TnT concentrations (hs-TNT < 50ng/L) would have been classified as normal by the conventional TnT assay. Among these patients, hs-TnT concentrations were also associated with mortality. - Limitations - The study of patients with type 2 diabetes may limit generalizability. These findings have not been externally validated. - Conclusions - In patients with type 2 diabetes mellitus receiving hemodialysis, cardiac TnT is associated with long-term mortality and cardiovascular outcomes. Concentrations of TnT not measurable with acceptable precision using a conventional TnT assay were associated with a poor prognosis when measured using a high-sensitivity assay.
Gesehen am 13.10.2020